2022
DOI: 10.1192/bjp.2021.221
|View full text |Cite
|
Sign up to set email alerts
|

Reconceptualising the treatment gap for common mental disorders: a fork in the road for global mental health?

Abstract: Summary In this analysis, we argue that the ‘treatment gap’ for common mental disorders often reflects lack of demand, arising because services fail to address the needs of disadvantaged communities. We propose a route forward for global mental health, with explicit focus on action on the socioeconomic determinants of psychological suffering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 24 publications
3
24
0
Order By: Relevance
“…A recent systematic review exploring the impact of socio-economic status (SES) on anti-depressant treatment outcomes highlighted that lower SES could lead to differential outcomes, even in the context of clinical trials when access to medication is guaranteed ( Elwadhi and Cohen, 2020 ). From the patient perspective, evidence from high-income settings suggests that many prefer psychological treatments over medications ( Dorow et al , 2018 ), and recent arguments about the nature of the treatment gap suggest that social interventions may be more in line with the voiced needs of many marginalized groups, alongside, or instead of, medicalized supports ( Roberts et al , 2022 ). Future studies should explore with communities where CM is practiced, what forms of intervention are best suited to their local contexts and communities.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review exploring the impact of socio-economic status (SES) on anti-depressant treatment outcomes highlighted that lower SES could lead to differential outcomes, even in the context of clinical trials when access to medication is guaranteed ( Elwadhi and Cohen, 2020 ). From the patient perspective, evidence from high-income settings suggests that many prefer psychological treatments over medications ( Dorow et al , 2018 ), and recent arguments about the nature of the treatment gap suggest that social interventions may be more in line with the voiced needs of many marginalized groups, alongside, or instead of, medicalized supports ( Roberts et al , 2022 ). Future studies should explore with communities where CM is practiced, what forms of intervention are best suited to their local contexts and communities.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, talking to a mental health professional was perceived as more helpful by higher SES individuals. As potential explanations, talking therapy might be better tailored to the needs of those higher education 27 and might more readily provide perceivable progress for individuals without poverty related pressures 13 . In conclusion, these findings point to a global 'triple inequality effect', whereby disadvantages of lower SES individuals deepen along each of the three health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Two systematic reviews using studies from the US and Europe showed that the effectiveness of psychological therapies 11 and antidepressant treatments 12 is lower for low SES individuals. As an explanation, lower SES individuals might face more socio-economic stressors which cannot be relieved by treatment 13 .…”
Section: Socio-economic Factorsmentioning
confidence: 99%
“…On the other hand, it may also be the case that communitybased care does not go far enough in addressing the social de terminants of mental health. While many communitybased care models focus on individuals with a mental disorder and their immediate family, very few address the fundamental structural drivers of men tal illness in populations, such as inequal ity, poverty, food insecurity, violence, and hazardous living conditions 111,112 . Suc cessful communitybased mental health services arguably require the existence of viable communities.…”
Section: Deinstitutionalization and Community Mental Health Carementioning
confidence: 99%